Karakteristik Biochar Limbah Bubuk Kopi Produksi UMKM Kopi Tirtoyudo, Malang Selatan - Faradila, Razhika; Harsono, Soni Sisbudi; Lasari, Yuni (Jurnal Ilmiah Teknologi Pertanian Agrotechno; Vol 9 No 2 (2024), 2025)
The coffee waste which generated from most cafeshop in South Malang is still not optimally utilized, this can be seen from the accumulation of coffee waste around the processing site. This research is an initiation from the research team to provide knowledge and trust to Tirtoyudo Coffee SME stakeholders in increasing the use value of coffee groud waste and circular economy. In general, the aim is to provide information related to the burning quality of coffee powder waste biochar through proximate analysis and socialization related to processing coffee waste into alternative energy, namely biochar. From the research conducted, it resulted in coffee ground waste (SCG) Biochar with a temperature of 500 o C having the best composition with a value of 9.33% moisture content, 4.08% ash content, 9.55 pH, and 13.15% C-Organic. This is because coffee has a good composition to restore nutrients and drying is carried out before run-off biochar. This research activity is expected to provide insight and expertise to the community, especially Tirtoyudo Coffee SME stakeholders in South Malang in order to develop biochar renewable energy technology from coffee powder waste (Spent Coffee Ground) into an alternative to using fuel that is more efficient, affordable and environmentally friendly. Anstrak Limbah yang dihasilkan dari sebagian besar UMKM kopi di Malang Selatan ini masih belum dimanfaatkan secara optimal, hal ini dapat dilihat dari menumpuknya limbah kopi di sekitar tempat pengolahan. Penelitian ini merupakan inisiasi dari tim peneliti untuk memberikan pengetahuan dan kepercayaan terhadap pelaku UMKM Kopi Tirtoyudo dalam meningkatkan nilai guna Limbah Kopi dan ekonomi sirkular. Secara umum tujuannya memberikan informasi terkait kualitas pembakaran biochar limbah bubuk kopi melalui analisis proksimat dan sosialisai terkait pengolahan limbah kopi menjadi energi alternatif yaitu biochar. Dari penelitian yang dilakukan menghasilkan Biochar Limbah Kopi dengan suhu 500 o C memiliki komposisi terbaik dengan nilai kadar air 9,33%, kadar abu 4,08%, pH 9,55, C-Organik 13,15% dan zat terbang 14,55%. Hal ini dikarenakan kopi memiliki komposisi yang baik untuk mengembalikan unsur hara dan dilakukan pengeringan sebelum run-off biochar.Kegiatan penelitian ini diharapkan dapat memberikan wawasan dan keahlian kepada masyarakat khususnya pelaku UMKM Kopi Tirtoyudo di Malang Selatan agar dapat mengembangkan teknologi energi terbarukan biochar dari limbah bubuk kopi (Spent Coffee Ground) menjadi alternatif penggunaan bahan bakar yang lebih efisien, murah dan ramah lingkungan.